PENEGAKAN HUKUM DAN PEMBUKTIAN HUKUM TERHADAP TINDAK PIDANA PEMBAKARAN HUTAN DAN LAHAN DI DESA BUKIT KERIKIL BENGKALIS RIAU - Suryono, Ramli (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2018)
RAMLI SURYONO, NIM: 1410245821, Law Enforcement and Legal Proof of Crime of Forest and Land Burning in Bukit Kerikil Village Bengkalis Riau, supervised by Firdaus and Erdianto.There are findings that become problems in the law enforcement of forest and land fires in Bukit Kerikil Village, Bukit Batu Sub-district, Bengkalis Regency, among others are people's awareness of lack of land clearance, arrears of Police Report mostly is about forest and land fire not exist witnesses who saw the burning so that the case was difficult to advance, the people caught were only those who were at the wrong place and time, as well as proof of forest and land fires cost a lot to ask for expert information. Before the proof is implemented, it takes a lot of money to do water bombing.The type of this research is sociological law research. Judging from its nature, this research is descriptive, that is describe clearly and detail about law enforcement and legal proof of crime of forest and land burning in Bukit Kerikil Village of Bengkalis Riau.Law enforcement on the crime of forest and land burning in Bukit Kerikil Village Bengkalis Riau has not been implemented properly although the legal proof of the crime is not essentially difficult. This is influenced by the difficulty of determining the status of land ownership on fire, the difficulties in the absence of witnesses, enormous enforcement costs, the distance to the location of land burned very far and the difficulty of access by land. There are no obstacles in law enforcement on the crime of forest and land burning in Bukit Kerikil Village Bengkalis Riau in terms of legislation and law enforcement apparatus. Factors that affect or become obstacles in law enforcement are facilities or facilities that support law enforcement, community factors and cultural factors. While the main obstacle in legal proof of the crime of burning forest and land in Bukit Kerikil Village Bengkalis Riau is the minimal cost to conduct investigation and investigation, especially in requesting expert information. The solution to overcome obstacles in law enforcement and legal proof of forest and land burning crimes in Bukit Kerikil Village Bengkalis Riau is the enhancement of facilities or facilities that support law enforcement, increase public awareness of law and eliminate cultures that harm the environment. The main solution in legal proof of the crime of forest and land burning in Bukit Kerikil Village Bengkalis Riau is the increase of investigation and investigation costs, especially in the case of requesting expert information.